2004
DOI: 10.1038/nm1125
|View full text |Cite
|
Sign up to set email alerts
|

The RAB25 small GTPase determines aggressiveness of ovarian and breast cancers

Abstract: High-density array comparative genomic hybridization (CGH) showed amplification of chromosome 1q22 centered on the RAB25 small GTPase, which is implicated in apical vesicle trafficking, in approximately half of ovarian and breast cancers. RAB25 mRNA levels were selectively increased in stage III and IV serous epithelial ovarian cancers compared to other genes within the amplified region, implicating RAB25 as a driving event in the development of the amplicon. Increased DNA copy number or RNA level of RAB25 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
419
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(440 citation statements)
references
References 25 publications
11
419
2
4
Order By: Relevance
“…We [31,42,55] and others [39,43] have previously demonstrated that genes significantly overexpressed when amplified are likely amplicon drivers, as the expression of these genes is required for the survival of cells harbouring amplification of their genomic region. Our integrated analysis has not only identified genes previously shown to be potential drivers of amplicons 8p11.2 (FGFR1), 8q24 (MYC), 11q13 (CTTN, FADD), 17q12 (ERBB2) and 20q13 (AURKA), but also identified a list of 269 that should be investigated as potential therapeutic targets in the amplicons on chromosomes 1q, 3q, 6p, 8q, 13q, 14q, 17q, 19q and 20q (Table 4; Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We [31,42,55] and others [39,43] have previously demonstrated that genes significantly overexpressed when amplified are likely amplicon drivers, as the expression of these genes is required for the survival of cells harbouring amplification of their genomic region. Our integrated analysis has not only identified genes previously shown to be potential drivers of amplicons 8p11.2 (FGFR1), 8q24 (MYC), 11q13 (CTTN, FADD), 17q12 (ERBB2) and 20q13 (AURKA), but also identified a list of 269 that should be investigated as potential therapeutic targets in the amplicons on chromosomes 1q, 3q, 6p, 8q, 13q, 14q, 17q, 19q and 20q (Table 4; Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that expression of genes consistently overexpressed when amplified may be required for the survival of cells harbouring amplification of their genetic loci [31,39,42,43]. To identify the likeliest drivers of the amplicons 8p11.2-p12, 8q24, 11q13.3, 17q12-q21 and 20q13.3, we first retrieved the genes mapping to these amplicons, performed a Pearson's correlation to determine those whose expression correlate with copy number and then identified all genes that were overexpressed when amplified within each region using a Wilcoxon sign rank test (Fig.…”
Section: Identification Of Likeliest Amplicon Drivers Of Recurrent Ammentioning
confidence: 99%
“…Ligands of avb3-integrin and b3 subunit silencing appear to drive EGFR into a complex with RCP and a5b1, and potentiated EGF-binding induced EGFR autophosphorylation and activation of downstream Akt. This finding might go some way towards explaining the pro-survival and antiapoptotic effects of Rab25 observed earlier [Cheng et al, 2004], which were not obviously related to integrin dynamics.…”
Section: Rabs Integrin Traffic and Cancer Cell Adhesion/migrationmentioning
confidence: 68%
“…Unlike Rab21, Rab25's role in cancer is much better established, particularly in epithelial cancers. It has been identified as the driver in the 1q22 genomic amplification associated with poor disease-free survival rate following surgical and chemotherapy procedures of a group of ovarian cancer patients [Cheng et al, 2004]. Rab25 over-expression in tumor cells resulted in a marked increased in anchorage-dependent colony forming activity, cell proliferation survival under apo-ptotic stress conditions and tumorigenesis in nude mice.…”
Section: Rabs Integrin Traffic and Cancer Cell Adhesion/migrationmentioning
confidence: 99%
“…Recently, RAB25 on 1q22 and IKBKE on 1q32 were shown to be functional oncogenes in ovarian and breast cancers by both overexpression and RNAi studies [28,29]. Presumably, both RAB25 and IKBKE, the latter encoding an IkappaB kinase that activates the NF-kB pathway, are likely driver genes for the gain of the q arm of chromosome 1, which is one of the most frequent genetic events in human cancer -occurring in 50% of breast, liver, lung, ovarian and other tumor types.…”
Section: Copy Number Alteration Profilingmentioning
confidence: 99%